The Role of the Family Environment on the Formation of Children's Personality in Keli Village, Keo Tengah Sub-District, Nagekeo District - Rince Pawe; Rodja Abdul Natsir; Bertholomeus Jawa Bhaga (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
This research discusses the role of the family in shaping children's personality in Keli Village, Central Keo District, Nagekeo Regency. The method used is qualitative with primary data collection through observation, interviews, and documentation on three families, one community leader, and one village official. Secondary data were obtained from books, journals, and articles. Interviews were conducted face-to-face to explore information related to the role of the family environment in children's personality development. Data analysis was conducted by reducing, presenting, and drawing conclusions based on field notes. The results showed that family has an important role in shaping children's personality. Children who grow up in harmonious families with sufficient love and attention tend to have positive personalities, such as confidence, responsibility, and courtesy. Conversely, children who receive less attention from their families have the potential to show a closed or aggressive attitude. This research emphasizes the importance of the family environment as the first educational institution that determines a child's future.